Источник СВЧ излучения с прямым умножителем частоты кварцевого генератора - Орел, Олександр Миколайович; Орел, Александр Николаевич; Orel, Oleksandr; Власой, И. Д.; Орел, Н. А. (ОЛДІ-ПЛЮС, 2017)
RU: В работе представлены результаты разработки высокостабильного источника СВЧ излучения дециметрового диапазона для лечения костных патологий c.-х. животных. TN: In the work presents the results of the development of a high-stable microwave source of the decimeter range for the treatment of bone pathologies in farm animals.
Source of microwave radiation with direct frequency frequency of quartz generator
Keywords: костная патология; электромагнитные колебания; стабильность частоты; спектр выходного канала; умножитель частоты; bone pathology; electromagnetic oscillations; frequency stability; output channel spectrum; frequency multiplier